PROTECTIVE FEATURES OF LOBOPHORA VARIEGATA METHANOLIC EXTRACT (LVME) ON COGNITIVE BEHAVIOUR AND REDOX HOMEOSTASIS IN N-NITROSODIETHYLAMINE TREATED DROSOPHILA MELANOGASTER - AJITHA, ADAIKKALM; SUBRAMANIAN, PERUMAL (International Journal of Current Pharmaceutical Research, 2022)
Objective: The protecting influence of methanolic extract of seaweed (Lobophora variegata) on cognitive as well as biochemical indices in N-Nitrosodiethylamine (NDEA, a potent carcinogen) treated Drosophila melanogaster is evaluated. Methods: In this study, Flies are divided into four groups; group 1–(control), group 2-flies were treated with 0.01% NDEA in food medium, group 3–with 0.01% NDEA and 0.01% Lobophora variegata methanolic extract (LVME) and group 4-with 0.01% LVME alone. Results: Behavioural abnormalities (negative geotaxis, phototaxis, smell and taste chemotaxis, hygrotaxis and thermotaxis) were quantitatively deviated in NDEA treated flies compared to control but were tend to be normalized in LVME treated flies. The contents of protein carbonyl, thiobarbituric acid reactive substance (TBARS), protein thiol and lipid peroxides were noticeably augmented in NDEA treated flies than control flies and correspondingly tend to normalize in LVME treated groups. Further, superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase (GST), glutathione peroxidase (GPX) and reduced glutathione (GSH) were decreased in NDEA treated group and were significantly increased (p<0.05) in LVME treated groups. Conclusion: It is well known that seaweed extracts contain numerous beneficial phytochemicals in abundantly. From our investigation, we found that the 0.01% LVME is efficient in reverting the abnormal behaviours and restoring the redox homeostasis of NDEA induced carcinogenesis in Drosophila melanogaster. Our investigation indicates that these phytochemicals could prevent the abnormalities in behaviour and redox homeostasis during carcinogenesis in D. melanogaster.